Selective BuChE Inhibitory Activity, Chemical Composition, and Enantiomeric Content of the Essential Oil from Salvia leucantha Cav. Collected in Ecuador - Gabriela Villalta; Melissa Salinas; James Calva; Nicole Bec; Christian Larroque; Giovanni Vidari; Chabaco Armijos (Plants, 2021)
The essential oil (EO) of Salvia leucantha Cav. was isolated by steam distillation of the aerial parts collected in the South of Ecuador. Its physical properties were evaluated and the chemical composition of the oil was determined by GC-MS and GC-FID analyses using two chromatographic columns, DB-5ms and HP-INNOWax. Six major compounds were identified, namely, the sesquiterpenes 6.9-guaiadiene (19.14%), (E)-caryophyllene (16.80%), germacrene D (10.22%), (E)-β-farnesene (10.00%), and bicyclogermacrene (7.52%), and the monoterpenoid bornyl acetate (14.74%). Furthermore, four pairs of enantiomers were determined by enantioselective GC-MS of the essential oil. (−)-germacrene D and (+)-α-pinene showed the highest enantiomeric excess (ee%). In an in vitro assay, the essential oil demonstrated an interesting inhibitory activity of the enzyme butyrylcholinesterase (BuChE), with an IC50 = 32.60 µg/mL, which is the highest determined for a Salvia species. In contrast, the oil was weakly active against acetylcholinesterase (AChE) with an IC50 > 250 µg/mL.